Comprehensive study on compositional modification of Tb3+ doped zinc phosphate glass - Syed Yaacob, Syariffah Nurathirah (Elsevier Masson SAS, 2018)
Series of glass composition (60-x) P2O5 -40 ZnO –(x) Tb2O3 where x = 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 mol % are prepared by conventional melt quenching technique. X-Ray Diffraction (XRD), FTIR, UV-Vis-NIR and the photoluminescence (PL) spectroscopy are used to characterize the physical, structural and optical behavior of the glass sample. The XRD pattern confirms the amorphous nature and DTA verified the thermal stability of all the glass samples. Glass with 1.5 mol % of Tb2O3 possesses the highest thermal stability. Glass density is found to increase proportionally with increasing amount of Tb3+ while the molar volume behaves reversely. Six main IR absorption bands centered at about 540, 748, 891, 1085 and 1294 cm− 1 are evidenced. The UV-Vis NIR absorption spectra reveals the absorption center band at about 540, 376, 488 and 1920 nm corresponding to the absorption from 7F6 ground state to various excited state of Tb3+ ion. The optical band gaps for direct and indirect transition are in the range 4.53–5.07 eV and 4.30 eV-4.56 eV respectively. The Urbach energy decreases with the increasing concentration of Tb2O3. The PL emission spectra reveals several prominent peaks at 413, 435, 457, 488, 540, 585 and 620 nm due to electronic transition from 5D3→7F5, 5D3→7F4, 5D3→7F3, 5D4→7F6, 5D4→7F5, 5D4→7F3 and 5D4→7F5 respectively.